Tissue engineering applications of bacterial cellulose based nanofibers - (:unkn) unknown (Springer, 2020)
Bacterial cellulose derived extracellularly by specific bacterial genera is an environmentally friendly polymeric material. The structural properties of bacterial cellulose are greater to those of herbal cellulose, as BC possesses novel features such as high purity, high crystallinity, nanostructure networks, good light transmittance, remarkable mechanical properties, stress–strain characterization and in situ formability, porosity, uniformity, inherent biocompatibility, and improvement of cell enhancing, separation, and proliferation. In recent years, bacterial cellulose has many opportunity purposes in different applications in biomedicine such as wound-dressing materials, medical membranes, biosensors, regeneration of organs, pharmaceutical industries, food, and cosmetics. Herein, the potential applications of bacterial cellulose, alone or in combination with different components, have been focused on for the use in the regenerative and tissue engineering as an implant and scaffold. © Springer Nature Singapore Pte Ltd 2020.
Keywords: Bacterial cellulose; Biomedical; Composites; Natural polymer; Tissue engineering